O movimento da RBS TV na articulação do social com o promocional - Andres, Fernanda Sagrilo (2012)
In the current context, companies from many s egments try to show themselves sensitive to the problems that affect society as a whole. In the communication area, one can notice the release of media products that highlight the company's social responsibility, through possible traces of self promotion. In the case of media companies, it is known that these always promoted themselves: they don't talk anything without talking about themselves before. Based on these observations, this study aims to verify, through a methodological process based on Greimasia n semiotics, the role developed by a regional station, affiliated to a national, when it enables, in it's productions, the joint between social and promotional. This is possible by examining the discursive strategies of the order of temporalization, themat ization, figurativization, actorialisation and toning, and communicative strategies, external to the text, employed by RBS TV station for this purpose. For this, it was made an approximation of "social" and "promotional" terms, employed by commercial broad casters who want greater sustainability in the market. The body of the analysis is composed by nine videos (socio-institutional actions) of five social campaigns develope d by the company, Rede Brasil Su l de Televisão, in a nine year interval. The choice of the afilliate of Rede Globo de Televisão is justified by the peculiarities of the broadcasters that need to combine confidence and identity with viewers, despite operating with a restricted space for local production and subordinate of the prodution of th e head network